1997
DOI: 10.1074/jbc.272.17.11171
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Acceptor Proteins by UDP-D-xylose Proteoglycan Core Protein β-D-Xylosyltransferase

Abstract: The formation of chondroitin sulfate is initiated by xylosyltransferase (XT) transferring xylose from UDPxylose to consensus serine residues of proteoglycan core proteins. Our alignment of 51 amino acid sequences of chondroitin sulfate attachment sites in 19 different proteins resulted in a consensus sequence for the recognition signal of XT. The complete recognition sequence is composed of the amino acids a-a-a-a-G-S-G-a-b-a, with a ‫؍‬ E or D and b ‫؍‬ G, E, or D. This sequence was confirmed by determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
61
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 42 publications
3
61
0
Order By: Relevance
“…Another possibility is the effect of the peptide sequence of the core protein on the enzyme recognition. A currently proposed GAG attachment motif is the Ser-Gly-Ser-Gly sequence and surrounding acidic amino acids (39,40). CSGalNAcT-2 might recognize CS binding peptide sequences of core proteins other than syndecan-4.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is the effect of the peptide sequence of the core protein on the enzyme recognition. A currently proposed GAG attachment motif is the Ser-Gly-Ser-Gly sequence and surrounding acidic amino acids (39,40). CSGalNAcT-2 might recognize CS binding peptide sequences of core proteins other than syndecan-4.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that xylosyltransferase is the rate-limiting enzyme in glycosaminoglycan addition [30,43]. Only a small percentage of Ii is normally modified by CS addition, potentially due to deviation of the Ii sequence from the xylosylation consensus sequence [44]. Modification of the Ii sequence to conform more closely to the consensus sequence (Figure 1) resulted in approx.…”
Section: Discussionmentioning
confidence: 99%
“…3-fold greater levels of Ii-CS. Modification of the amino acids surrounding the xylose-accepting serine residue probably changed the conformation of the protein, potentially affecting the activity of xylosyltransferase, which has been shown to be dependent on protein conformation [44]. However, it is also possible that changing the primary structure around the xylose-accepting serine residue could also affect the activity of other enzymes needed to complete the tetrasaccharide linkage region, thus increasing glycosaminoglycan addition.…”
Section: Discussionmentioning
confidence: 99%
“…The mutations did not appear to affect other acidic species that were perturbed by nitrous acid treatment, suggesting that Nudel contains other sites for GAG attachment. Near the three mutated sites, Nudel contains three copies of the sequence SG, which has been shown to be sufficient for GAG attachment (Brinkmann et al, 1997).…”
Section: Discussionmentioning
confidence: 99%